Investigando o impacto das mudanças climáticas sobre a produtividade e o serviço de polinização em Caryocar brasiliense - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The production of fruits in agricultural crops is the result of several external factors that contribute to increase productivity over time. For instance, the pollination ecosystem service performs the exchange of gametes among plant individuals, increasing the reproductive rate of these species. However, climate change can alter the distribution of plants and pollinators, leading to a spatial incompatibility that can result in a lower rate of visitation and, consequently, fruit production. “Pequi” (Caryocar brasiliense) is a plant species endemic and widely distributed in the Brazilian Cerrado. It is pollinated by two nectarivorous bats (Anoura geoffroyi and Glossophaga soricina) also with broad distributions throughout the Neotropical region. Our aim is to evaluate if climatic changes can alter the distribution of these species, causing a spatial incompatibility between plants and pollinators. The second objective is to evaluate if future scenarios of climate change can compromise the productivity of “Pequi” fruits. In order to evaluate the effect of climatic changes on productivity and pollination service in this plant, we performed the Ecological Niche Modeling. In these models, species occurrence records are usually used to extract a range of environmental tolerance where species are able to survive, and after that, it is estimated that adequate areas are based on this information. We found that climate change does not have a very strong effect on the distribution of the plant and its pollinators. Thus, our result indicates that pollination service remains in future scenarios of climate change. The same is true when we evaluating only productivity. In our results, it was possible to observe only a retraction of areas with high productivity in scenarios of climate change. This may indicate that climate change does not have a very large effect on its distribution, and consequently its productivity. Therefore, “Pequi” can be a profitable crop according to the climate projections we use.
Investigating the impact of climate changes about the productivity and pollination service in Caryocar brasiliense
Keywords: Serviço de polinização; Produtividade; Economia; Modelagem de Nicho Ecológico; Pollination service; Productivity; Economy; Ecological Niche Modeling; CIENCIAS BIOLOGICAS